2012
DOI: 10.19153/cleiej.15.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering Steady Advances for an Extreme Programming Course

Abstract: This paper presents an empirical study about identifying improvement actions for an eXtreme Programming course in the academic environment. This exploratory study is undertaken in two preliminary phases. These phases are part of a wider research project to develop a theory about how to continuously improve courses of similar structure and content. The first phase consists of diagnosing improvement actions from the 2010 edition of the course through a qualitative analysis of data obtained u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 19 publications
0
13
0
2
Order By: Relevance
“…This practice is also freely applied in training classes [7], in coaching sessions and in agile conferences. The topics for discussion may be exposed through a quick presentation or by leaving the topics in boards for further grouping together.…”
Section: Discussion Groupsmentioning
confidence: 99%
See 4 more Smart Citations
“…This practice is also freely applied in training classes [7], in coaching sessions and in agile conferences. The topics for discussion may be exposed through a quick presentation or by leaving the topics in boards for further grouping together.…”
Section: Discussion Groupsmentioning
confidence: 99%
“…After preliminary qualitative studies [7] [8], we identified that the above practices are successfully applied in coaching and training sessions for enhancing learning in agile academic and corporate environments.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations